Spatial Heterogeneity of Coupling Coordination Development between Logistics and Economy in Central Plains of China - Guangliang Zhou; Congyu Zhao; Ming Wu; Yu Chen; Fuli Zhou (Discrete Dynamics in Nature and Society)
The coupling of logistics and economy is of great significance for regional development. To promote the regional development of urban agglomeration in Central Plains of China, this paper attempts to study the spatial divergence of coupling development and the influential factors. The 30 urban cities in Central Plains of China have been regarded as the research objects. We develop an integrated framework to derive the coupling degree between logistics and economy in this region including linear weighting method, coupling coordination degree model, and exploratory spatial data analysis. The spatial pattern of the coupling coordination degree between logistics and economy is studied by the visualization evolution analysis. In addition, the GWR model is formulated to study the influential factors of regional coupling development. The results show that (1) the integrated development level of logistics industry and economy in the Central Plains City Cluster is low, and the development difference between regions is significant; (2) the overall coupling and coordination level of logistics industry and economy in the Central Plains City Cluster is not high and is at the stage of imminent disorder; in space, it presents a spatial pattern of “high in the center and low around”; (3) the coupling coordination degree around each region and city is a strong positive spatial correlation and agglomeration situation significantly; (4) the ranking of the influence degree of each driving factor from high to low is urbanization rate; science and technology level; education level; and population density.